2016
DOI: 10.1186/s13148-016-0224-3
|View full text |Cite
|
Sign up to set email alerts
|

Sirtuin functions and modulation: from chemistry to the clinic

Abstract: Sirtuins are NAD+-dependent histone deacetylases regulating important metabolic pathways in prokaryotes and eukaryotes and are involved in many biological processes such as cell survival, senescence, proliferation, apoptosis, DNA repair, cell metabolism, and caloric restriction. The seven members of this family of enzymes are considered potential targets for the treatment of human pathologies including neurodegenerative diseases, cardiovascular diseases, and cancer. Furthermore, recent interest focusing on sir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
222
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 303 publications
(245 citation statements)
references
References 117 publications
1
222
0
1
Order By: Relevance
“…Although STACs have therapeutic potential, certain diseases, such as cancer in certain contexts and Parkinson disease, may benefit from sirtuin inhibition (reviewed in REF. 179). EF2, elongation factor 2; FOXO, forkhead box O; HNGB1, high-mobility group box 1; IL, interleukin; LXR, liver X receptor; MMP9, matrix metalloproteinase 9; NF-κB, nuclear factor-κB; NLRP3, NOD-, LRR- and pyrin domain-containing 3; PGC1α, peroxisome proliferator-activated receptor-γ co-activator 1α; PPAR, peroxisome proliferator-activated receptor; STAT5, signal transducer and activator of transcription 5; TGFβ, transforming growth factor-β; UCP2, mitochondrial uncoupling protein 2.…”
Section: Figurementioning
confidence: 99%
“…Although STACs have therapeutic potential, certain diseases, such as cancer in certain contexts and Parkinson disease, may benefit from sirtuin inhibition (reviewed in REF. 179). EF2, elongation factor 2; FOXO, forkhead box O; HNGB1, high-mobility group box 1; IL, interleukin; LXR, liver X receptor; MMP9, matrix metalloproteinase 9; NF-κB, nuclear factor-κB; NLRP3, NOD-, LRR- and pyrin domain-containing 3; PGC1α, peroxisome proliferator-activated receptor-γ co-activator 1α; PPAR, peroxisome proliferator-activated receptor; STAT5, signal transducer and activator of transcription 5; TGFβ, transforming growth factor-β; UCP2, mitochondrial uncoupling protein 2.…”
Section: Figurementioning
confidence: 99%
“…Notably, intense efforts have been made over the last decade to develop sirtuin-activating compounds, or STACs. Dozens of SIRT1 activators have been tested in animal models of diabetes, neurodegeneration, and other aging-related pathologies, and one STAC, SRT2104, has progressed to Phase 2 human patient clinical trials [34, 35]. By contrast, the development of SIRT6-selective compounds is at an earlier stage, and no SIRT6-activating small molecules are as yet available.…”
Section: Heterochromatin Silencing and Genome Maintenance In Aging Anmentioning
confidence: 99%
“…Computational studies indicate that NAM inhibition of SIRT3 involves apparent competition between the inhibitor and the enzyme cofactor NAD + while the inhibition of other sirtuins activity was non-competitive[117]. More detailed review on sirtuins inhibitors and activators is found in[99,118]. More studies are needed to develop more potent and specific activators and inhibitors of sirtuins activity.…”
Section: Role Of Sirtuins In Nafldmentioning
confidence: 99%